Thinking and killing : philosophical discourse in the shadow of the Third Reich - Segev, Alon (de Gruyter, 2013)
This book explores the phenomenon of the Third Reich from a philosophical perspective. It concentrates on how Nazi Germany, the Holocaust and Anti-Semitism are conceived by eight German thinkers from the Continental tradition, exposing and then exploring the tension between ideology and philosophy, between submission to authority and genuine critical thinking, which constitute the essence of the Continental philosophical tradition. Alon Segev, Hebrew University of Jerusalem, Israel.